On the Frequency of Oronasal Fistulation After Primary Cleft Palate Repair. (November 2019) - Tache, Ana; Mommaerts, Maurice Y.
Objective: The aims of the study were to assess the postoperative oronasal fistula rate after 1-stage and 2-stage cleft palate repair and identify risk factors associated with its development. Design: Systematic review. Setting: Various primary cleft and craniofacial centers in the world. Patients, Participants: Syndromic and nonsyndromic cleft lip, alveolus, and palate patients who had undergone primary cleft palate surgery. Intervention: Assessment of oronasal fistula frequency and correlation with staging, timing, and technique of repair, gender, and Veau type. The results obtained in this systematic review were compared with those in previous reports. Outcome: The main outcome is represented by the occurrence of the oronasal fistula after 1-stage versus 2-stage palatoplasty. Results: The mean fistula percentage was 9.94%. In the Veau I, II, III, and IV groups, the respective fistula rates were 2%, 7.3%, 8.3%, and 12.5%. Oronasal fistula locations based on the Pittsburgh Fistula Classification System were soft palate (type II), 16.2%; soft palate–hard palate junction (type III), 29.3%; and hard palate (type IV), 37.3%. There were no statistically significant differences between 1-stage and 2-stage palatoplasty, syndromic and nonsyndromic, or male and female patients. Primary palatoplasty timing was not a significant predictor. Conclusion: Some disparities arose when comparing studies, mainly regarding location and types of clefting prone to oronasal fistulation. Interestingly, the fistula rate does not differ between 1- and 2-stage closure, and timing of the repair does not play a role.